2021
DOI: 10.1093/jn/nxaa400
|View full text |Cite
|
Sign up to set email alerts
|

Poor Taste and Smell Are Associated with Poor Appetite, Macronutrient Intake, and Dietary Quality but Not with Undernutrition in Older Adults

Abstract: Background Age-related declines in taste and smell function are widely assumed to contribute to the decrease in appetite and the development of undernutrition in older adults. Objectives Here we aim to assess the associations of both taste and smell function with several nutrition-related outcomes in a single study, with poor appetite and undernutrition as primary outcomes. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 55 publications
2
31
0
Order By: Relevance
“…In agreement, we observed that those with OD had diets that were more energy dense, in addition to being lower in diet quality. Our diet quality findings among U.S. adults 40 years and older largely conform with findings from findings from Dutch and Australian older adults, which also reported poorer diet quality related to OD [29,37]. Notably, analyses from the Korean NHANES [30] suggest that dietary associations with OD were particularly evident among younger and middle-aged women.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…In agreement, we observed that those with OD had diets that were more energy dense, in addition to being lower in diet quality. Our diet quality findings among U.S. adults 40 years and older largely conform with findings from findings from Dutch and Australian older adults, which also reported poorer diet quality related to OD [29,37]. Notably, analyses from the Korean NHANES [30] suggest that dietary associations with OD were particularly evident among younger and middle-aged women.…”
Section: Discussionsupporting
confidence: 83%
“…Descriptive analyses of differences in participant characteristics and dietary measures between the two groups were tested using surveyweighted chi-square tests (for categorical variables) or t-tests (for continuous variables). Given known differences in OD and dietary intake by age and sex [26,29,30], we created age/sex categories (males 40-64 years, males ≥65 years, females 40-64 years, and females ≥65 years) a priori to stratify associations between olfactory function and dietary measures. Supplementary Table S1 summarizes the demographic, clinical, and lifestyle characteristics by the four age/sex categories.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike for sight and hearing, no corrective means such as lenses or hearing aids exist to compensate for dimishments in taste and smell, making secondary complications in areas relating to taste and smell more likely. Accordingly, taste and smell impairment have been shown to affect numerous aspects of everyday life such as reduced appetite [6] and mood changes and depression [7,8], and reduced quality of life, particularly of clinical populations [QoL; 9,10].…”
Section: Introductionmentioning
confidence: 99%